y = 2
you must know how to do these by now
2006-09-17 07:51:42
·
answer #1
·
answered by Joe_Floggs 3
·
0⤊
0⤋
5 - 4(y + 1) = 3
5 - 4y - 4 = 3
The distributive prlperty on the left side of the equation
1 - 4y + 4y = 3 + 4y
Addintion property. adding + 4y to both sides of the equation
Collecting like terms on the left side of the equation
1 = 3 + 4y
1 - 3 = 3 + 4y - 3
Subtraction property. Subtracting - 3 from both sides of the equation
-2 = 4y
-2/4 = 4y/4
Dividing both sides ty 4
-1/2 = y
2006-09-17 15:11:57
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
5 - 3 = 4(y + 1 )
2 = 4 (y+1)
2/4 = y+1
1/2 = y +1
1/2 - 1 = y
-1/2 =y
so y = -1/2
2006-09-17 14:58:54
·
answer #3
·
answered by anahona 2
·
0⤊
0⤋
5-4[y+1] =3
5-4y-4=3
1-4y=3
-4y=2
y= - 2/4 = -1/2
2006-09-17 15:59:13
·
answer #4
·
answered by teaser 2
·
0⤊
0⤋
Use distributive property: 5 - 4y - 4 = 3
Combine like terms: 1 - 4y = 3
Solve (opposite operations): subtract 1 on both sides: -4y = 2
Divide by -4 on both sides: Y = -1/2
2006-09-17 14:54:12
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
Use the distributive rules:
5-4(y+1)=3
5-4y+1=3
Now take like numbers to the same side
5-4y+4=3
9-4y=3
-4y=-6 (I subtracted 9 from both sides)
y=1.5 (divide through both sides by -4)
2006-09-17 14:54:00
·
answer #6
·
answered by john977 2
·
0⤊
0⤋
5 - 4y - 4 = 3
1 - 4y = 3
4y = -2
y = - 1/2
2006-09-17 14:56:59
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
so...
4(y+1) = 2
y+1 = .5
y = -.5
2006-09-17 15:25:00
·
answer #8
·
answered by animal 2
·
0⤊
0⤋
5-4y-1=3
4-4y=3
-4y=-1
y=1/4
2006-09-17 15:03:08
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
you have asked almost the same problem four times today!!!!
better learn to solve it by yourself...
all your problems are of the form: a + by = c
so by =c-a or y = (c-a)/b
just substitute a,b,c values....!!
2006-09-17 15:03:40
·
answer #10
·
answered by m s 3
·
0⤊
0⤋